Chapter In kind wages between city and countryside: Northern Italy in the Eighteenth Century - Ongaro, Giulio; MOCARELLI, LUCA (Firenze University Press, 2025)
The paper aims at clarifying the characterisation and the role played by in-kind payments in wages’ composition both in the cities and in the countryside in Eighteenth century Northern Italy. Case studies mainly from Bologna, Padua, and Milan, and their countryside will be taken into consideration. We will propose some figures to understand which was (approximately) the level and the percentage of the in-kind part of adult male wages in the cities and countryside, also observing how these figures changed according to the various tasks to be accomplished. We will also analyse possible changes of the values across time and in different areas. We will also characterize the in-kind part of the payments, observing which products and in which amounts the various workers received.